Revolução em Karl Marx e Antonio Gramsci: entre estratégias de classe e partido - Costa, Bruno Augusto da (2022)
This dissertation aims to reflect on the historical process of strategy through scientific socialism, founded by Karl Marx (1818 – 1883) and Friedrich Engels (1820 – 1895). To this end, we analyze the accompaniments of the Marxist tradition, especially from the work of Antonio Gramsci (1891 - 1937), as well as some contributions from Lenin (1870 - 1924), Rosa Luxemburgo (1871 - 1919) and István Mészáros (1930 – 2017). We adopted as a methodology the bibliographic review and the historical-dialectical materialism or the philosophy of praxis, in the language of Gramsci. We use the category of class struggle as the guiding thread of the exhibition, with which we seek to integrate the research lines of Political Philosophy and Philosophy of History. We also mobilize the perspectives of authors such as Georg Lukács (1885 - 1971), Eric Hobsbawm (1917 - 2012), Domenico Losurdo (1941 - 2018), among other Marxist exponents. We define historical-dialectical materialism as a tool that is simultaneously revolutionary and an instrument for examining reality. In this sense, we understand that it is a non-dogmatic set of ideas and that it uses both the critique of the capitalist model and the self-criticism of the working class' experiences of power, fueled by the search for human emancipation. You see that the essence of historical-dialectical materialism is an investigation of concrete events in the faith that we can learn from our strategic abandonment of perspectives associated with proletarianism or degradation in the totalitarian state. The contemporary strategy perspective points to the need for a new community system. It was based on the construction of another economic-political mode of production, engendered by social relations, but fair, egalitarian and self-conscious, creating, portero, another subjectivity. Finally, we attest that historical-dialectical materialism remains viable and able to think and transform reality through its philosophical premises.